2002
DOI: 10.1159/000048027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Volume Preloading on Uteroplacental and Fetal Circulation during Spinal Anaesthesia for Caesarean Section in Uncomplicated Singleton Pregnancies

Abstract: Objective: Effects of volume preloading during spinal anaesthesia for elective caesarean section on maternal blood pressure, feto-maternal circulation and fetal outcome. Patients and Methods: In a pilot study a randomised trial was performed in 22 healthy women with uncomplicated, singleton pregnancies at 36–40 weeks of gestation undergoing elective caesarean section under spinal anaesthesia. In the low volume group (group A) patients received 150 ml of crystalloid solution for preloading, in the high volume g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…It increases the duration of analgesia, intensify the motor block and prolongs the duration of postoperative analgesia but it can cause hypotension and bradycardia. 8 The present study was underwent to combine two adjuvants to local anaesthetics with the purpose to improve the quality of subarachnoid block.…”
Section: Introductionmentioning
confidence: 99%
“…It increases the duration of analgesia, intensify the motor block and prolongs the duration of postoperative analgesia but it can cause hypotension and bradycardia. 8 The present study was underwent to combine two adjuvants to local anaesthetics with the purpose to improve the quality of subarachnoid block.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal anaesthesia is the preferred anaesthetic technique for elective operative delivery and is also commonly used for unplanned Caesarean section [1]. Spinal-induced hypotension remains the most important side effect with a reported incidence between 20 and 100% [2][3][4]. Hypotension can cause maternal discomfort (nausea and vomiting) [2] and impaired utero-placental perfusion, resulting in fetal acidemia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In maternal population, low-dose spinal anesthesia produces less maternal hypotension and fetal acidosis due to decreased uteroplacental blood flow compared with conventional dose regimes. Hypotension is the common complication with an incidence of 20%-100% in maternal population undergoing to caesarean section (5,13,14). Previous studies have shown that reduction at doses used for spinal anesthesia is related with increased hemodynamic stability and doses of intrathecal bupivacaine between 5 mg and 7 mg are sufficient to provide effective anaesthesia (1).…”
Section: Discussionmentioning
confidence: 99%